THE ROLE OF RELIGIOUSITY AN INCREASE MANIFEST NEEDS AND PRODUCTIVITY OF HUMAN RESOURCES - Arizqi, Arizqi (IJIBE (International Journal of Islamic Business Ethics), 2016)
This study aimed to examine the effect of religiosity on the manifest needs which consists of need for achievement, need for power, need for affiliation. In addition, this study also aims to examine how the manifest needs role in triggering an increase in labor productivity of Human Resources.The research was conducted by testing SEM (Structural Equation Modeling) with the help of statistical software SmartPLS. The study was conducted using a survey by distributing questionnaires to 79 lecturers remain functional positions (JAFA) Sultan Agung Islamic University. In determining the amount of the sample number of researchers using the formula slovin with proportional random sampling technique.The results showed that religiosity have significant influence on the improvement of manifest needs, and then to increase productivity of human resources can be improved through increasing of manifest need in dimension need for achievement, while the need for power and the need for affiliation are not able to explain the productivity of the organization.